2014
DOI: 10.1089/sur.2013.032
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Adherence to Different Meshes Used in Abdominal Surgery

Abstract: Depending on the type of bacteria, collagen-coated hydrophilic prostheses with a large surface increased bacterial adherence significantly. These differences should be taken into consideration when choosing a mesh graft, which limits infection in abdominal wall reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Our results showed that, despite no significant differences, the numbers of bacteria adhered to the surface of the PP meshes were lower for Op than Surg. This finding is consistent with those reported by others [17,18] who have shown that macroporous PP meshes display less bacterial adhesion than materials with a smaller pore size. Interestingly, both PP meshes showed the significantly greater adhesion of both strains than Precl.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results showed that, despite no significant differences, the numbers of bacteria adhered to the surface of the PP meshes were lower for Op than Surg. This finding is consistent with those reported by others [17,18] who have shown that macroporous PP meshes display less bacterial adhesion than materials with a smaller pore size. Interestingly, both PP meshes showed the significantly greater adhesion of both strains than Precl.…”
Section: Discussionsupporting
confidence: 93%
“…This means that biosynthetic prosthetic implants show similar in vitro behaviour in response to infection. This has also been observed by other authors for composite meshes [18,20], which usually induce higher bacterial loads than non-absorbable polymer implants despite having a surface biodegradable film.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The main pathogenic factor of prosthetic joint infections is the development of a bacterial biofilm. This structure allows bacteria to resist antimicrobial agents and immune responses [5], so patients with this type of infection require a longer period of antibiotic therapy and repeated surgical procedures [6,7].…”
Section: Introductionmentioning
confidence: 99%